Face off - Hagberg, David (Hagberg, David. Kirk McGarvey adventures., 2018)
New York Times bestselling author David Hagberg is particularly adept at crafting compelling and timely thrillers. Face Off is no exception; this novel will appeal directly to his core audience, though as with the rest of this series, readers need not be familiar with McGarvey to enjoy it. Kirk McGarvey is lunching in the Eiffel Tower when terrorists attempt to bring the Paris icon down. He springs into action to stop the attack, only to find there's a much larger plot at stake. One that aims to force the incompetent US President out by pitting him against Russia. But Vladimir Putin is eager to avoid World War III. When a missing Russian nuclear weapon is found heading to the US, Putin enlists McGarvey's help to stop it. The stakes couldn't be higher, and the outcome couldn't be more in doubt. Only McGarvey stands a chance of intervening before it's too late, in a race against time across Paris, Istanbul, Moscow, and Washington, D.C.